How Do Involved Communication and Leadership Affect Readiness For Change Through Organizational Identification in Public Sector? - Rino Afriantoro; Aryana Satrya (Syntax Literate, 2022)
Changes in the external environment demand that public organizations respond and adapt to enhance public services. In addition to examining the effect of involved communication and leadership on change readiness, the purpose of this study is to investigate the mediating influence of organizational identification in the public sector. The information was acquired through a web-based questionnaire of 387 tax service employees scattered throughout Indonesia. Application Lisrel 8.8 was used in order to verify the hypotheses. All hypotheses positive relationships are statistically significant in the results. The findings of this study indicate that organizational identification mediates not only the relationship between involved communication and change readiness but also the transformational leadership and change readiness relationship. This paper's research is limited to small percentage of public service employees, which may not have fully captured the development of the phenomena being studied. In a public sector undergoing change, the implementation of involved communication, transformational leadership, and organizational identification will impact and positively contribute to employee readiness for change.